School networks: Being and creating networks. A framework for analyzing the forms, processes, and practices of school networks for pedagogical and didactic innovation - Alessia Lambicchi; Giulia Gabriella Elena Pastori (Ricerche di Pedagogia e Didattica, 2025)
The literature highlights school networks as key drivers of change and professional development. However, despite growing interest in these forms of collaboration, there is a lack of analytical tools to support their effective development. This article introduces an analytical matrix, developed as part of a PhD research project, which offers a systematic approach to analyzing school networks. Structured across fourteen dimensions, the matrix serves as a research and analysis tool to help networks critically assess their structure and operational processes. The paper presents a theoretical framework that precedes an empirical study aimed at refining and validating the matrix.